Introduction to chemical engineering computing - Finlayson, Bruce A. (New Delhi Wiley, 2013)
Each chapter in Introduction to Chemical Engineering computing contains a descrition of the physical problem in general terms and in a mathematical context, thorough step-by-step instructions, numerous examples, and comprehensive explanations for each problem and program. This indispensable text features Excel, Matlab, Aspen Plus, and Femlab programs and acquaints readers with the advantages of each.
Introduction. - - Equations of state. - - Vapor-liquid equilibrium. - - Chemical reaction equilibrium. - - Mass balances with recycle streams. - - Simulation of mass transfer equipment. - - Process simulation. - - Chemical reactors. - - Transport processes in one dimension. - - Fuid flow in two and three dimensions. - - Convective diffusion equation in two and three dimensions.
Include appendix and index. - - Appedndix A. Hints when using excel. - - Hints when using Matlaba. - - C. Hints when using aspen plus. - - Hints when using Femlab. - - E. Parameter estimation. - - F. Mathematical methods.